Particle fluxes by subtropical pelagic communities under ocean alkalinity enhancement - P. Suessle; J. Taucher; S. U. Goldenberg; M. Baumann; K. Spilling; K. Spilling; A. Noche-Ferreira; A. Noche-Ferreira; M. Vanharanta; M. Vanharanta; U. Riebesell (Biogeosciences)
Ocean alkalinity enhancement (OAE) has been proposed as a carbon dioxide removal technology (CDR), allowing for long-term storage of carbon dioxide in the ocean. By changing the carbonate speciation in seawater, OAE may potentially alter marine ecosystems with implications for the biological carbon pump. Using mesocosms in the subtropical North Atlantic, we provide first empirical insights into impacts of carbonate-based OAE on the vertical flux and attenuation of sinking particles in an oligotrophic plankton community. We enhanced total alkalinity (TA) in increments of 300 µmol kg−1, reaching up to ΔTA = 2400 µmol kg−1 compared to ambient TA. We applied a pCO2-equilibrated OAE approach; i.e., dissolved inorganic carbon (DIC) was raised simultaneously with TA to maintain seawater pCO2 in equilibrium with the atmosphere, thereby keeping perturbations of seawater carbonate chemistry moderate. The vertical flux of major elements, including carbon, nitrogen, phosphorus, and silicon, as well as their stoichiometric ratios (e.g., carbon-to-nitrogen ratios), remained unaffected over 29 d of OAE. The particle properties controlling the flux attenuation, including sinking velocities and remineralization rates, also remained unaffected by OAE. However, we observed abiotic mineral precipitation at high OAE levels (ΔTA = 1800 µmol kg−1 and higher) that resulted in a substantial increase in particulate inorganic carbon (PIC) formation. The associated consumption of alkalinity reduces the efficiency of CO2 removal and emphasizes the importance of maintaining OAE within a carefully defined operating range. Our findings suggest that carbon export by oligotrophic plankton communities is insensitive to OAE perturbations using a CO2 pre-equilibrated approach. The integrity of ecosystem services is a prerequisite for large-scale application and should be further tested across a variety of nutrient regimes and for less idealized OAE approaches.